The Effect of Book-Tax Difference and Profit Management on Profit Growth in Manufacturing Companies Listed on the Indonesia Stock Exchange - suhendri (PT FORMOSA CENDEKIA GLOBAL, 2023)
Industrial development in Indonesia makes every existing company compete to advance the company. Every company has a main goal, namely to obtain and increase company profits every year. This research design uses a quantitative descriptive approach, aiming to determine the relationship between two or more variables (Winarno 2013: 67). This research discusses the Effect of Book-Tax Difference and Earnings Management on Profit Growth in Manufacturing Companies Listed on the Indonesia Stock Exchange. Based on the results of hypothesis testing for the Book-Tax Difference (X1) variable, it is known that the tcount is 2.802718 with a significance level of 0.0255. This shows that tcount is greater than ttable (2.802718 > 1.671) with a significance value (0.0255 <0.05). So it can be concluded that the Book-Tax Difference (X1) has a significant positive effect on Profit Growth (Y).